Senderización y señalética turística de la Cascada “Chaca Capac” de la Parroquia Salvias del Cantón Zaruma, Provincia de El Oro - Granda Reyes, Gloria Jacovina (2017)
Tourism is very important not only from the social and cultural point of view, but also from the economic point of view. Thanks to tourism, it significantly increases investment in infrastructure and buildings, generating a higher level of development in the areas involved. The means of transport are usually improved in quality and frequency, as well as currency increases, unemployment rates decrease significantly, generating greater welfare in affected communities. The Ministry of Tourism of Ecuador, in accordance with the guidelines and objectives of the 2020 travel plan, decided to design a comprehensive signaling and common guidance structure for national and foreign tourists who provide easy and efficient access to each destination, In order to improve security, information and their travel time, allowing them to use each place better The aim of this research work is improving the tourism in the parish, it is for that reason to carry out the thesis called “SENDERIZACION AND SIGNALING TOURIST OF THE WATERFALL “CHACA CAPAC” SALVIAS PARISH ZARUMA CANTON, EL ORO PROVINCE” whose purpose is the conservation and protection of natural attractions, through the implementation of trails and signage, in that way each of the green áreas are protected to care for natural resources. People who like the nature, peace and tranquility. It is a perfect place for looking the birds and butterflies. also you can make camping, hiking, riding horse and photography. La Cascada Chaca Capac is located in the Salvias Parish about 45 minutes from the city, from there you can access by car to the Tambillo sector and then 45 minutes walking to the first waterfall and one hour to back; It is an appropriate place for watching birds and butterflies. Also you can make camping, hiking, riding horse and photography in that way it pretends give a contribution to tourism development in order to ensure and guarantee good living in the habitants. The general objetive of the research was: To draw up the Senderización and signaling for Chapa Capac waterfall of Salvias Parish, Zaruma Canton, El Oro province As specific objectives: To Develop a situational tourism diagnosis of Salvias Parish, Zaruma Canton El Oro Province; To propose the senderización and signaling of Chaca Capac waterfall; and finally to elaborate environmental impact study of the path Chapa Capac waterfall. The methodology was developed based on the performance of each proposed objectives that were different methods and techniques; In the first objective were used sources such as collection bibliographic and primary sources such as direct observation, field research and interviews., Also worked with the inventory chips of tourist attractions of the MINTUR and Summary chips and FODA Matrix. In the second objective was made with the collection of information which used some tools such as the use of GPS which allowed collect points and coordinates the design of the maps the path; to determine the load capacity it was made by Miguel Cifuentes autor; about the signage was designed strictly of the Manual Tourist Señalética the Ministry of Tourism. Finally in the third obective was made a study of environmental impact where was applied Leopold matrix Quantitative and qualitative which gave us the same result e size of environmental impact that occurred in the Project. In conclusion Salvias parish counts with an important variety of tourist attractions to promote tourism development, the same that need to be appropriate and potentiated by the relevant authorities. This place does not have signals that allow tourists guided correctly, it affects tourism activity therefore the proposal of senderización and signage helps in a positively way, it will contribute to the protection and conservation of it, also it will offer a quality service when you visit it. For that reason recommended to GAD of the parish, through agreements with MINTUR carry out projects that are related to the field of tourism, also make the agreements necessary to improve tourism infrastructure and tourist signage in order to attract demand of tourists whether local, national and international.